2021
DOI: 10.3390/en14175243
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Glazing on the Functioning of a Trombe Wall Containing a Phase Change Material

Abstract: Among the technological solutions for external walls, the Trombe wall is an interesting proposition for obtaining solar radiation energy. The aim of the presented research is to determine the influence of glazing parameters on the thermal performance of the Trombe wall containing a phase change material (PCM). In the experimental tests, three glazing (G1, G2, and G3) with different heat transfer coefficient (Ug) and total solar energy transmittance factor (g) were used. The tests were carried out under laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For this reason, the solution for some of these limitations is readymade thermal energy batteries, which often form part of active heat and cold distribution systems. Some examples of PCM use in combination with opaque partitions, as described by Lichołai et al [59], are shown in Figure 6.…”
Section: Phase Change Materials In Opaque Partitionsmentioning
confidence: 99%
“…For this reason, the solution for some of these limitations is readymade thermal energy batteries, which often form part of active heat and cold distribution systems. Some examples of PCM use in combination with opaque partitions, as described by Lichołai et al [59], are shown in Figure 6.…”
Section: Phase Change Materials In Opaque Partitionsmentioning
confidence: 99%
“…Moreover, the high thermal inertia allows for exploiting the stored thermal energy also at night. One or more transparent covers allow for separating the absorbing surface from the external environment to limit thermal losses [32], forming an air gap in which the thermo-circulation occurs (see Figure 1). The transparent surface is equipped with an overhang opportunely sized to create shading in summer.…”
Section: Trombe Wall Operationmentioning
confidence: 99%
“…Materials with high thermal mass, such as masonry or concrete, can store and release heat effectively. The type of glazing used on the outer surface of the Trombe wall affects the amount of solar radiation transmitted [8,9]. Low-emissivity (low-e) glass can help control heat transfer.…”
Section: Introductionmentioning
confidence: 99%